Control of anisotropic conduction of carbon nanotube sheets and their use as planar-type thermoelectric conversion materials. Issue 1 (31st December 2021) - Matsumoto, Masamichi; Yamaguchi, Ryohei; Shima, Keisuke; Mukaida, Masakazu; Tomita, Motohiro; Watanabe, Takanobu; Ishida, Takao; Fujigaya, Tsuyohiko
ABSTRACT: The large anisotropic thermal conduction of a carbon nanotube (CNT) sheet that originates from the in-plane orientation of one-dimensional CNTs is disadvantageous for thermoelectric conversion using the Seebeck effect since the temperature gradient is difficult to maintain in the current flow direction. To control the orientation of the CNTs, polymer particles are introduced as orientation aligners upon sheet formation by vacuum filtration. The thermal conductivities in the in-plane direction decrease as the number of polymer particles in the sheet increases, while that in the through-plane direction increases. Consequently, a greater temperature gradient is observed for the anisotropy-controlled CNT sheet as compared to that detected for the CNT sheet without anisotropy control when a part of the sheet is heated, which results in a higher power density for the planar-type thermoelectric device. These findings are quite useful for the development of flexible and wearable thermoelectric batteries using CNT sheets. Graphical abstract: uf0001